Periapical status in patients affected by osteoporosis: A retrospective clinical study. Issue 5 (14th June 2022) - Cadoni, Erika; Ideo, Francesca; Marongiu, Giuseppe; Mezzena, Silvia; Frigau, Luca; Mela, Quirico; Capone, Antonio; Duncan, Henry F.; Cotti, Elisabetta
Abstract: Objectives: To assess the periapical status in patients with osteoporosis (OP) treated with denosumab (D), bisphosphonates (BPs), or not on medication, and to understand if these conditions influence the prevalence and the progression of apical periodontitis (AP). Material and Methods: Seventy‐six patients with OP alone or treated with D, or BPs, formed the study group (O), and those from 76 patients matched for age and sex, without diseases, and not taking medications, constituted the control (C) in this retrospective case−control study. The data from the complete clinical and radiographic examination, medical history, decayed, missing, and filled teeth (DMFT), and periapical index score (PAI) were recorded for each patient. Wilcoxon rank test, χ 2, and Student's t test were used as appropriate. Results: The prevalence of AP was similar in O and C. Furthermore, AP was significantly more frequent in root canal‐treated teeth in O patients ( p  = .03). Conclusions: OP does not appear to be associated with the development of AP. Moreover, the increased prevalence of AP in root canal‐treated teeth in O patients highlights a possible relationship between the healing dynamics of the disease post‐therapy and the patients' medication. A larger sample is needed to confirm these findings.